New Techniques for Diagnosis and Treatment of Musculoskeletal Tumors: Methods of Intraoperative Margin Detection. Issue 3 (September 2018) - Catanzano, Anthony A.; Ryan, Sean P.; Lazarides, Alexander L.; Brigman, Brian E.; Eward, William C.
Abstract : Although frozen section analysis remains the standard for intraoperative margin detection for some cancers, there are critical limitations with using this method in the treatment of musculoskeletal tumors. Extensive work has been done to develop more accurate methods of intraoperative assessment of resection margins. Successful limb-salvage surgery requires adequate resection of tumor without excessive resection of normal tissue. Traditional imaging modalities such as computed tomography, magnetic resonance imaging, and positron emission tomography scans have been adapted for use with computer navigation to provide more accurate intraoperative assessment and resection. However, these modalities are not without their own disadvantages, such as cost and availability. Newer technologies are being investigated to evaluate tumors intraoperatively at the microscopic and molecular level using spectroscopy and fluorescence imaging. Despite the promise of these intraoperative modalities, there are limited long-term outcome studies to validate their efficacy. In this symposium, we discuss the current advances in modalities for intraoperative margin assessment and their application in treating musculoskeletal tumors. In addition, we outline the existing evidence, albeit limited, of their short, and long-term successes.